Construction of titanium dioxide nanorod/graphite microfiber hybrid electrodes for a high performance electrochemical glucose biosensor. Issue 17 (19th April 2016) - Zhang, Jian; Yu, Xin; Guo, Weibo; Qiu, Jichuan; Mou, Xiaoning; Li, Aixue; Liu, Hong
Abstract : The demand for a highly sensitive and selective glucose biosensor based on microfiber hybrid electrodes which can be used for implantable or on-time monitoring is constantly increasing. Abstract : The demand for a highly sensitive and selective glucose biosensor which can be used for implantable or on-time monitoring is constantly increasing. In this work, TiO2 nanorods were synthesized in situ on the surface of graphite microfibers to yield TiO2 nanorod/graphite microfiber hybrid electrodes. The TiO2 nanorods not only retain the high activity of the immobilized glucose molecule, but also promote the direct electron transfer process on the electrode surface. As a working electrode in an electrochemical glucose biosensor in a flowing system, the microfiber hybrid electrodes exhibit high sensitivity, selectivity and stability. Due to its simplicity, low cost, high stability, and unique morphology, the TiO2 nanorod/graphite microfiber hybrid electrode is expected to be an excellent candidate for an implantable biosensor or for in situ flow monitoring.